Letter from the Guest Editor. (21st January 2014) - Davis, Cameron
<x content-type="archive" xml:space="preserve">Abstract</x> The Great Lakes hold some 90% surface-water supply in the United States (US) and about one fifth of the fresh surface water on Earth. As a result, the Great Lakes have immense environmental, economic, and cultural significance, especially for the roughly 42 million people who live, work, and recreate in the Great Lakes Basin.